Analisis Faktor Yang Berpengaruh Terhadap Profitabilitas Perusahaan Manufaktur Yang Terdaftar Pada Indeks Saham Syariah Indonesia Tahun 2011-2015 - MUHAMMAD NURUL QOMARUDDIN, 041114022 (Departemen Ekonomi Syariah, FEB, Universitas Airlangga, 2018)
The purpose of this study is to analyze the impact of Days Inventory, Days Receivable, Days Payable, Leverage . Debt to Equity Ratio, Current Ratio on Manufacturing Firms profitability in Indonesian Sharia Stock Index by 2011 until 2015. The problems in this research gap from former Research and the business gap phenomenon from the Manufacturing Firms over period 2011-2015. Therefore a deeper research to observe the problems which influence Return on Assets with reasonable theory Research variables consisted of six independent variables and 1 dependent variable is profitability (ROA). Data analysis technique to answer research problem and examine research hypothesis using Panel Data Regression Analysis. Data obtained from Indonesian Stock Exchange published via Website real time, obtained 30 data samples. Based on the research, known that the effect of Days Payable on Manufacturing Firms profitability partially significant. Meanwhile, other independent variables partially not significant. Other hand the effect of all six independent variable simultaneous significant effect on Manufacturing Firms profitability